Development of a Pharmacy Residency Research Certificate Program. (April 2021) - Weeda, Erin R.; Weant, Kyle A.
Background: Similar to teaching certificate programs, which have been incorporated in many pharmacy residencies to improve teaching skills, resident research certificate programs could provide residents with more exposure to biostatistics and research design. However, few research certificate programs have been described.Objective: To assess the impact of a research certificate program on residents' attitude toward, confidence in, and knowledge of research.Methods: A resident research certificate program was created for the 2018-2019 residency class at our institution, which included 33 pharmacy residents (15 postgraduate year-1 [PGY1] and 18 PGY2 residents). The program consisted of 7 sessions aimed at providing residents with research training. To earn a certificate, participants were required to attend 6 or more sessions and achieve a score greater than or equal to 70% on a postassessment. An optional questionnaire assessing attitude, confidence, and knowledge was also administered at baseline and following the certificate program.Results: Of the 33 residents participating in the research certificate program, 21 (9 PGY1 and 12 PGY2) residents completed both the baseline and follow-up questionnaire and were included in the analysis. All items assessing attitude and 3 of 6 items assessing confidence improved significantly following the certificate program when compared to baseline ( P < .05 for all). Median knowledge scores were no different on the baseline versus follow-up questionnaire ( P = .54).Conclusions: After completing a research certificate program, resident knowledge scores did not differ from baseline, but attitudes toward research and confidence appeared to improve. Research certificate programs could be an avenue for providing pharmacy residents with increased exposure to and comfort with biostatistics and research design.